Wealth of man - "Jay, Peter" (New York, 2000)
Road to Riches is the story of the rise and fall of whole economies and nations, and the ascent of man as the only economic animal - as producer, consumer and accumulator of wealth. Ideas about the story of the wealth of man are constantly changing. Peter Jay explains how the economic machine works and how far beyond our control it really is. Peter Jay has spent his working life in both Britain and America, following and explaining the day-to-day twists and turns of fortune throughout the world. As he searches for deeper explanations of the forces that disturb our complacency and change our lives, he has felt the need to reach further back into history to find more enduring truths about complexities of economic patterns.
Keywords: Wealth - history